2010
DOI: 10.1080/03003930.2010.506979
|View full text |Cite
|
Sign up to set email alerts
|

Local Expenditure Interaction in Italian Municipalities: Do Local Council Partnerships Make a Difference?

Abstract: This paper investigates interdependence among local councils in Italy in their public spending and distinguishes between possible sources of this interdependence. We find significant positive interaction among neighbouring local councils in regard to both spending at the level of total expenditure and spending on different sub-categories. Attempts to identify the source of this horizontal interaction seem to reject the yardstick competition hypothesis. Addressing the role that local council partnerships may pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
1
32
0
2
Order By: Relevance
“…The summary statistics of the above-mentioned variables are reported in table 2. Although in the regression analysis we take the logarithm of both dependent and control variables, to partially remove problems of heteroschedasticity which affect data on public expenditures in the region Marche (Ermini and Santolini, 2010).…”
Section: Datamentioning
confidence: 99%
“…The summary statistics of the above-mentioned variables are reported in table 2. Although in the regression analysis we take the logarithm of both dependent and control variables, to partially remove problems of heteroschedasticity which affect data on public expenditures in the region Marche (Ermini and Santolini, 2010).…”
Section: Datamentioning
confidence: 99%
“…Lastly, the study that is the closest to ours is led by Ermini and Santolini (2010). They investigate the impact of inter-jurisdictional agreements in Italy on the extent of spending interactions, focusing on specific categories of expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…Correlational studies have revealed that interactions between public service expenditures by local governments can be driven by various effects, including 1) financial competition between regions (Besley and Coate 2003;Wilson and Wildasin 2004;Sheng and Fu 2006), 2) mimicking that is driven by yardstick competition (Thenbürger 2002;Frederico 2003;Gebremeskel 2012;Caldeira 2012), and 3) positive or negative spillovers (Dalhby 1994;Conley and Dix 1999;Sato 2000;Boadway 2001;Brueckner 2003). Both theory and causal observations suggest that expenditure spillovers are a widespread feature of many services provided by local governments (Ermini and Santolini 2010;Sole-Olle 2006). These earlier findings constitute the basis of our research; however, previous research has focused on the description and statistical analysis of spatial disparities in public services but has ignored spatial correlation in public service supply.…”
Section: Introductionmentioning
confidence: 95%